2017
DOI: 10.1364/oe.25.020216
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved local reflectance spectra measurements in full-field optical coherence tomography

Abstract: Full-field optical coherence tomography (FF-OCT) is a widely used technique for applications such as biological imaging, optical metrology, and materials characterization, providing structural and spectral information. By spectral analysis of the backscattered light, the technique of spectroscopic-OCT enables the differentiation of structures having different spectral properties, but not the determination of their reflectance spectrum. For surface measurements, this can be achieved by applying a Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…To determine both parameters accurately, great care must therefore be taken during the data acquisition process. We previously demonstrated that the numerical aperture (NA) of the objectives could significantly modify the amplitude of the reflectance spectrum reconstructed from a FT of the fringes [16]. By keeping the NA fully open during the image stack acquisition, errors are induced in the amplitude of the spectrum and we then show that the determination of the refractive index is wrong, subsequently distorting the measurement of the thickness (Fig.…”
Section: Pmma Layermentioning
confidence: 83%
See 1 more Smart Citation
“…To determine both parameters accurately, great care must therefore be taken during the data acquisition process. We previously demonstrated that the numerical aperture (NA) of the objectives could significantly modify the amplitude of the reflectance spectrum reconstructed from a FT of the fringes [16]. By keeping the NA fully open during the image stack acquisition, errors are induced in the amplitude of the spectrum and we then show that the determination of the refractive index is wrong, subsequently distorting the measurement of the thickness (Fig.…”
Section: Pmma Layermentioning
confidence: 83%
“…For this first result, the refractive index was assumed to be constant in the model to speed up the algorithm. Usually spread over an area of 0.79 µm², the diffraction spot becomes more extended (2.27 µm²) because of the necessity of reducing the system NA, resulting in a lateral resolution that decreases from 0.5 µm to 0.85 µm [16].…”
Section: Pmma Layermentioning
confidence: 99%
“…[10][11][12] We have previously demonstrated that for depth-resolved spectral measurements, it is necessary to decrease the effective NA of the optical system, in this case by closing the aperture diaphragm, in order to reduce the errors that distort the results. [13] Consequently, the lateral resolution slightly decreases to 0.85 μm. For these kinds of measurements the notion of axial resolution is added.…”
Section: Transparent Samplesmentioning
confidence: 99%
“…Usually, the signal is selected using a window with a length which is approximately the same as that of the interferogram. [13] This gives a spectral resolution of 30 nm at a wavelength of 650 nm for both cases. The measurable wavelength range is set by both the illumination spectrum of the source and the spectral response of the camera.…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation